ANALISIS MENU DENGAN PENDEKATAN MATRIKS DI EBONI RESTAURANT AKHSAYA HOTEL KARAWANG, JAWA BARAT - Tatik Sriwulandari; Hadara Ramadhani (Bogor Hospitality Journal, 2021)
Menus drive purchasing and production decisions in all operations of a restaurant. Menu analysis allows restaurant owners to evaluate individual menu items systematically by comparing each menu item to other menu items based on pre-selected criteria. Historical menu analysis should include food costs, contribution margins and the popularity or mix of products over a given period. This research was conducted to analyze 24 maincourse menus in Eboni Restaurant Akhsaya Hotel Karawang, West Java. The analysis conducted is Menu Management with a matrix approach using three approaches, namely menu engineering, the percentage of cost of food approach to popularity and the contribution margin approach to the percentage of the cost of food. The results showed that the main course menu at Eboni Restaurant at Hotel Akhsaya Karawang has not produced optimal performance. Based on the three analyzes carried out, the results of the engineering menu analysis show that of the 24 main course menus analyzed, 4 menus (17%) are in the stars category, as many as 6 menus (25%) are in the plowhorses category, as many as 6 menus (25%) are in the puzzle category, and 8 menus (33%) are in the dog category. The results of the Percentage Analysis of Food Cost Percentage show that 5 menus (21%) are in the winners category, 5 menus (21%) are in the marginal II category, 4 menus (17%) are in the marginal III category, and 10 menus (42%) are in the losers category. The results of the contribution margin analysis with the cost of goods showed that of the 26 main course menus analyzed, 5 menus (21%) were in the prime category, as many as 5 menus (21%) were in the standard category, as many as 4 menus (17%) were in the category. sleepers, and 10 menus (42%) are in the problem category. The suggested strategies are as follows: maintaining menus in category I, increasing selling prices or making changes to standard recipes by reducing food costs for menus in category II, reducing selling prices and promoting more actively for category III menus and removing menu items in category IV.